2015
DOI: 10.1007/s12272-015-0696-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of zingerone on carbon tetrachloride- and dimethylnitrosamine-induced liver injuries in rats

Abstract: In this study, we investigated the hepatoprotective and anti-fibrotic effects of zingerone, one of the active components of ginger, against carbon tetrachloride (CCl4)- and dimethylnitrosamine (DMN)-induced liver injuries in rats, respectively. Oral administration of zingerone (10 mg/kg) reduced CCl4-induced abnormalities in liver histology, serum alanine aminotransferase and aspartate aminotransferase levels, and liver malondialdehyde levels. Zingerone treatment attenuated CCl4-induced increases in inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 28 publications
4
18
0
Order By: Relevance
“…In pathologic specimens, a reduced lamellar body expression pattern indicates severe lung injury that demonstrates decreased type II cells (33,41). In the current study, increased RAC and decreased thickness of the alveolar septa with remarkably reduced fibrosis and decreased SMA immunostaining, as well as better density of the lamellar body protein staining pattern, were present in the ginger-treated group (9)(10)(11)(12)(13)(14)(15)(16)(17)42). Additionally, during the BPD process, increased apoptosis in lung tissue cells has been demonstrated (43).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In pathologic specimens, a reduced lamellar body expression pattern indicates severe lung injury that demonstrates decreased type II cells (33,41). In the current study, increased RAC and decreased thickness of the alveolar septa with remarkably reduced fibrosis and decreased SMA immunostaining, as well as better density of the lamellar body protein staining pattern, were present in the ginger-treated group (9)(10)(11)(12)(13)(14)(15)(16)(17)42). Additionally, during the BPD process, increased apoptosis in lung tissue cells has been demonstrated (43).…”
Section: Discussionsupporting
confidence: 56%
“…Pups in the control group (21% O 2 for 14 days + placebo) and hyperoxia + LPS group (95% O 2 for 14 days + placebo) were administered oral saline (2 mL/kg), but pups in the hyperoxia + LPS + ginger group (95% O 2 for 14 days + ginger) were treated once a day from the first day of the study to the end of the study. In the present experiment, we used whole ginger since many different compounds in ginger have been determined to act in a synergic manner that suggests the importance of using whole ginger (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Preparation and Dosage Of Gingermentioning
confidence: 99%
See 1 more Smart Citation
“…One study indicated that the upregulation of myocardial pro-inflammatory genes (TNF-alpha, IL-1beta and IL-6) and coronary thrombosis in rats with myocardial infarct induced by isoproterenol were both stopped by zingerone pre-treatment [ 38 ]. Furthermore, another study on CC14-intoxicated rats reported an association between the hepatoprotective effect of zingerone and its inhibiting effect on inflammation via suppression of activation of upstream mitogen-induced protein protein kinases [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Red Ginger has many chemical components such as pungeant principles, gingerols and shogaol [10]. Ginger has been used for respiratory therapy [11], because it has several compounds which function as antioxidants, anti-inflamatory, anti-microbial and anti-fibrotic agents [12]- [14]. The aim of this study is to prove the effect of red ginger ethanol extract on blood MDA level of white male Wistar strain rats induced with cigarette smoke.…”
Section: Introductionmentioning
confidence: 99%